KEY CONCEPTS OF THE HISTORICAL DEVELOPMENT OF THE "RUSSIAN IDEA" IN A PHILOSOPHICAL ASPECT - Irina V. Khvoshchevskaia (Russian Studies in Culture and Society)
The author of the article presents a study on the dialectics of the universal spirit from the perspective of Russian philosophy. The interrelation of concepts such as "national spirit," "folk soul," "national self-consciousness," "national character," and others is analyzed. The significance of the "Russian idea" for Russian self-consciousness is shown, revealing the uniqueness of the worldview of the Russian people, basic traditional values, and the distinctive path of civilization development. A historical overview and the stages of the development of ideas about the "Russian idea" are provided, highlighting the peculiarities of the development of national self-consciousness.